PRELIMINARY OBSERVATIONS ON THE FISHERY OF BOMBAYDUCK HARPODON NEHEREUS IN THE GULF OF KUTCH - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
The fishery for Bombayduck in the Gulf of Kutch is well organised and isconducted on the pattern of that of Bombay and Saurashtra coasts. The totalBombayduck landings from the gulf are estimated between 8,000 to 10,000 tonnes;the major landing centres being Modhwa, Navinar, Bhadreshwar and Takkara.The boats engaged are Machchwa type and nonmechanised. The bag net, locallyknown as 'Gunja,' is used, which is similar to the 'dol' net. Raciation studies onsamples from Kutch and Jaifrabad revealed that the fish from these places differsignificantly in 6 morphometric characters